2010
DOI: 10.1111/j.1399-3062.2010.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of antiviral‐resistant human cytomegalovirus in heart and lung transplant recipients

Abstract: Immunocompromised transplant recipients are at high risk for human cytomegalovirus (CMV)-related infection and disease. Antiviral prophylaxis and treatment have reduced CMV morbidity and mortality, but at times promote development of antiviral-resistant CMV strains that can significantly contribute to adverse clinical outcomes in transplant recipients. We have investigated CMV genotypes in transplant recipients (bone marrow, stem cell, kidney, heart, lung, and liver) receiving antiviral prophylaxis or preempti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Cases of patients with dual UL97 and UL54 mutations are particularly prevalent in lung transplant recipients. A recent 39-patient study showed that lung transplant recipients accounted for 57% of patients with dual UL97 and UL54 mutations, even though that transplant procedure accounted for only 22% of CMV-positive patients (27). Several cases of multidrug-resistant, dual UL97/UL54 mutant CMV viruses have been reported in solid organ and stem cell transplant recipients (21,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of patients with dual UL97 and UL54 mutations are particularly prevalent in lung transplant recipients. A recent 39-patient study showed that lung transplant recipients accounted for 57% of patients with dual UL97 and UL54 mutations, even though that transplant procedure accounted for only 22% of CMV-positive patients (27). Several cases of multidrug-resistant, dual UL97/UL54 mutant CMV viruses have been reported in solid organ and stem cell transplant recipients (21,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…If a drug-resistant variant is identified in the UL97 gene, subsequent UL54 gene sequencing is recommended (19). Many cases of resistance have been documented, both as case reports (6,(20)(21)(22)(23)(24)(25)(26) and cohort studies (5,15,27). Most of these cases report resistance arising from canonical UL97 ganciclovir resistance mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]16,17,19,26 Antiviral resistant CMV strains also continue to emerge in 2-10% of treated solid organ transplant recipients. 7,[27][28][29][30][31] We undertook a five-year randomised study examining the efficacy of valGCV prophylaxis and preemptive therapy for prevention of CMV infection and disease following OLT at a tertiary referral hospital in Melbourne, Australia. We examined the importance of viral load, CMV genotype, antiviral resistance, herpesvirus co-infections, and host factors such as pre-transplant serostatus.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, fast genotyping of the viral polymerase requires 5 --7 working days, but owing to several limitations it is not yet established for the routine diagnostic setting. However, despite suspected symptoms and/or signs of HCMV disease by clinicians, HCMV DNA could not be detected in~20% of patients [1,3,12]. This often-observed discrepancy of treatment failure due to suspected viral resistance, but lacking of resistance mutations in genotypic assays or even viral DNA or pp65 antigenaemia, points to the requirement for well-directed diagnostic tools and better defined clinical symptoms of HCMV-associated disease.…”
Section: Expert Opinionmentioning
confidence: 99%
“…In conclusion, more studies are required on the dynamic of virus populations under drug pressure. Clinicians have to face the decision as to whether risking a re-exposure to the antiviral compound in relapses is reasonable or whether an evolution of HCMV-resistant virus in long-term patients should be feared [12,13].…”
Section: New Aspects For Early Detection Of Resistant Cytomegalovirusmentioning
confidence: 99%